2012
DOI: 10.1111/j.1528-1167.2012.03594.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in young adults who underwent resective surgery for epilepsy in childhood

Abstract: SUMMARYPurpose: This study investigated quality of life (QOL) in young adults who had undergone epilepsy surgery before the age of 16 years. The contribution to QOL of seizure status in the prior year, sex, number of antiepileptic drugs, and mood were evaluated. Methods: Sixty-nine young adults who had undergone surgery were subdivided into those who were seizure-free in the past year (n = 38) and those who had seizures (n = 31) in that time. A nonsurgical comparison group of young adults (n = 29) with childho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 51 publications
5
41
0
Order By: Relevance
“…Seizure freedom in children leads to improved intellectual and cognitive ability [36], better memory function [30], fewer behavioral problems [33], decreased medication use and side effects [25,34], and is the most important predictor of quality of life [9,31]. Survey data have also suggested that Engel class I outcome is associated with higher levels of education, employment status, independence, and overall satisfaction compared to less favorable seizure outcomes [25,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seizure freedom in children leads to improved intellectual and cognitive ability [36], better memory function [30], fewer behavioral problems [33], decreased medication use and side effects [25,34], and is the most important predictor of quality of life [9,31]. Survey data have also suggested that Engel class I outcome is associated with higher levels of education, employment status, independence, and overall satisfaction compared to less favorable seizure outcomes [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Given that intractable seizures can lead to significant morbidity and increased risk of death, temporal lobectomy is an important treatment option for medically refractory TLE [11,28]. Complete seizure freedom is the ultimate goal in pediatric TLE surgery, as it is the most important predictor of quality of life in epilepsy treatment [9,31]. Unfortunately, 10-40 % of children continue to have seizures after temporal lobectomy [32,35].…”
Section: Introductionmentioning
confidence: 99%
“…The total score was calculated by weighing and summing up the product of the subscale scores. Higher scores reflected better quality of life and lower scores worse quality of life [39,40]. 4 control subjects and 3 intervention group subjects belonged to the age group below 18 years, and hence the QOLIE-31 score scale was used among 33 control subjects and 37 subjects in the reflexology group.…”
Section: Primary Outcome Measures and Response Calculationsmentioning
confidence: 99%
“…About 10-50 % of the patients with DRE are amenable to surgical treatment [2]. The purpose of surgical resection is essentially seizure freedom, rather than seizure reduction as quality of life is linked to this outcome [3]. There are often additional benefits on neurodevelopment which can be considered a bonus and not a primary indication for surgery.…”
Section: Introductionmentioning
confidence: 99%